Identification of transient overvoltage using discrete wavelet transform with minimized border distortion effect and support vector machine / Saidatul Habsah Asman - Asman, Saidatul Habsah (2018)
The rapid growth of electric power industry today has changed the conventional framework as far as power quality issues are concerned. Power quality issues such as power quality disturbances can substantially affect high sensitive utilization equipment like the malfunction of sensitive electronic medical equipment and adjustable speed motor drives trip off-line.